(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2016)
Although many studies have emerged examining media representations of Muslims and Islam through the lens of discourse analysis, it is unfortunate that similar studies focusing on glocalised marketing strategies targeted at Muslims have been scarce, especially at a time when market research analysts have identified Muslims as constituting one of the fastest growing consumer segments in the world. In order to tap into this promising market, a number of cosmetics companies have left no stones unturned in their efforts to convince Muslim consumers that their products are Shariah-compliant. Whether or not this claim has any truth value, it is persuasive, as it raises awareness about the existence of halal cosmetics. In line with this, the present study examined the linguistic and non-linguistic semiotic features employed by the halal cosmetics companies to promote their products to Muslim consumers in order to expose the dominant discourses, underlying meanings and hidden ideologies. A qualitative research design was employed to study the marketing websites of five halal cosmetics companies. Analysis was carried out using Fairclough's (1992) three-dimensional model of critical discourse analysis. Findings call attention to the commodification of Islam, revealing how marketers are transforming cosmetics into powerful symbols representing religious correctness and values, indices of one's piety.